EFFECT OF BIOGAS DIGEST ON THE MICROBIAL POPULATION AND ENZYMATIC ACTIVITY OF SOIL UNDER CHICKPEA CULTIVATION - G. VENKATESWARA RAO, CH. SUJANI RAO, P. VENKATA SUBBAIAH*; M. SREE REKHA (The Journal of Research ANGRAU, 2019)
The experiment was conducted during Rabi, 2018 on black clayey soils to study the ‘Effect of biogas digest on biological properties of chickpea grown soil’using chickpea variety ‘JG-11’ in randomized block design and replicated thrice. The results revealed that application of 100% Recommended dose of Phosphorus (RDP) through BGD + microbial consortium recorded highest biological activity (bacteria, fungi, actinomycetes population and enzymatic activity) which was on par with treatment that received 100% RDP through biogas digest.